التعريف بالنظريات الفقهية وأهمية دراستها - بن هني ., قبلي (جامعة الوادي-university of eloued, 2015)
من الجدير بالاهتمام في الصياغات المعاصرة للفقه الإسلامي، انتظامه في نظريات مقننة تراعي فيها اجتماع الفروع التي تشترك في أبواب النظرية، تسهيلا لمعرفة تلك الأحكام للعامة والخاصة، وهو ما يتناسب مع الدوائر النظامية التي يقرب إليها الفقه بهذا النحو. حتى تمتثل الشريعة المنزلة، ويرد بها على المغرضين الذين يشككون في مصداقية الفقه الإسلامي. فالتنظير للحضارات وتراكيبها المختلفة تستلزم على علماء العصر سلوك نمط يثبت صورة الإسلام وتشريعاته السامية، وبهذا نكون قد قدمنا خدمة جليلة لديننا الحنيف. The Islamic jurisprudence (fiqh) is a worth to pay attention in our modern concepts, because its regularity is in the theories which is consider the grouping of branch with in the theory’s doors to simplify those rulings for both sides public and private. All that to protect the credibility of the Islamic jurisprudence, so the structure of different civilizations require the modern scholars to present and fix the Islam with its legislations .Hence, we have provided a great service for our religion
مقال
Keywords: نظريات فقهية - فقه إسلامي - تشريعات.; Jurisprudence theories - Islamic jurisprudence - Legislations.